Pola Spasial Penggunaan Kendaraan Pribadi untuk Mengevaluasi Rute Layanan Bus Rapid Transit di Provinsi Jambi - Muhammad Thias Adiyasa; Okto Risdianto Manullang (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2019)
Indonesian is a country that continues to improve so that the creation of mass transportation services in urban areas can be better. to attract the interest of urban communities to use mass transportation rather than private vehicles, the Government must be able to provide mass transportation facilities that can support community mobility in urban areas. Bus Rapid Transit (BRT) is one of the most popular solutions used in big cities in Indonesian. Transiginjai BRT in Jambi Province has 4 corridors, but only one corridor has been realized. in BRT Corridor 1 the Transiginjai loading factor does not reach the applicable standard (70%). Therefore, this study aims to evaluate the route of the Corridor Transiginjai BRT service based on the spatial pattern of self-owned vehicle use which is a representation of the demand pattern for community travel on the Transsiginjai BRT Corridor 1 route. The analytical method in this study is a quantitative descriptive approach with frequency distribution techniques and spatial modeling approaches, namely Spatial Statistics Analysis. The analytical tool used by using GIS (Geographic Information System). The results of this study showed 29% of households use cars and motorbikes, 21% use cars, and 31% use motorcycles. With a spatial pattern based on the overall spatial cluster that is formed high cluster